Forests and urban green areas as tools to address the challenges of sustainability in Latin American urban socio-ecological systems - Bonilla-Bedoya, Santiago (2020)
One sustainability challenge is confronting the process of global urbanization considering wellbeing and environmental justice. Integrating different disciplines to describe and analyze the relationships of urban socio-ecological systems gives us useful empirical tools to formulate policies and programs in urban planning considering their spatial dimension. The objective of this study is to present a model that integrates and explains the socio-ecological urban relations of a Latin American city considering three high-level approaches: forestry, geography, and psychology. Thus, we defined four factors: a) urban forest and green areas; b) urban spatial segregation; c) perceived restoration; and d) subjective wellbeing. For these, we grouped 16 measured variables and collected them with three specific procedures: a) SPOT remote sensors and object-based classification of urban coverage; b) analysis of geospatial data with census information; and c) field surveys. We applied descriptive multivariate statistics and also proposed a structural equation model (SEM) that integrates all the variables and data. We found that the factor “urban green areas” had a direct positive relationship with the factors “urban spatial segregation” and “perceived restoration.” We observed that urban green areas were meeting spaces between different socioeconomic categories, reducing segregation and multiplying opportunities for the psychological restoration of citizens. However, we found no evidence that green areas are related to subjective wellbeing. The model quantified the socio-ecological relationships produced by combining various factors of urban socio-ecological systems, suggesting the benefits of this method to generate knowledge towards planning and managing Latin American cities. Our results are encouraging in terms of environmental justice and wellbeing. In developing countries where forecasts indicate rising urban populations, the need to establish planning processes based on scientific information is vital to meet the challenges of sustainability in the twenty-first century. © 2020 Elsevier Ltd